QCD factorization for chiral-odd parton quasi- and pseudo-distributions - Vladimir M. Braun; Yao Ji; Alexey Vladimirov (Journal of High Energy Physics, 2021)
Abstract We study chiral-odd quark-antiquark correlation functions suitable for lattice calculations of twist-three nucleon parton distribution functions h L (x) and e(x), and also the twist-two transversity distribution δq(x). The corresponding factorized expressions are derived in terms of the twist-two and twist-three collinear distributions to one-loop accuracy. The results are presented both in position space, as the factorization theorem for Ioffe-time distributions, and in momentum space, for quasi- and pseudo-distributions. We demonstrate that the twist-two part of the h L quasi(pseudo)-distribution can be separated from the twist-three part by virtue of an exact Jaffe-Ji-like relation.